2022
DOI: 10.3389/fmicb.2022.801083
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Selection and Dispersal Limitation Dominate the Effect of Soil Strata Under Warming Condition

Abstract: Global warming is likely to affect the underground microbial communities in various ecosystems, but the response of soil microbial communities along a vertical depth profile to global warming has been elusive. Herein, we leveraged a warming field experiment in Qinghai-Tibet Plateau grassland and investigated the community structure of prokaryotes and fungi from the upper (0–15 cm) and lower (15–30 cm) strata under ambient and elevated temperature treatments. Three-years continual warming only significantly shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
2
1
0
Order By: Relevance
“…We also found that homogeneous selection played an important role in soil microbial community assembly (Figures 2a,b). This finding is supported by several recent studies and may be elucidated as follows (Wang, Feng, et al., 2022; Wang, Liu, et al., 2022; Zhao et al., 2022). First, farmlands typically experience frequent fertilization and disturbances (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…We also found that homogeneous selection played an important role in soil microbial community assembly (Figures 2a,b). This finding is supported by several recent studies and may be elucidated as follows (Wang, Feng, et al., 2022; Wang, Liu, et al., 2022; Zhao et al., 2022). First, farmlands typically experience frequent fertilization and disturbances (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…In the context of standard strawberry production practices, such uniform selective pressures could be from tillage, soil fumigation, or application of plastic tarps throughout the growing season (Bolda et al, 2015). Similar predominance of homogenous selection has also been observed in aquatic and terrestrial ecosystems, including agricultural soils (Allen et al, 2020;Barnett et al, 2019;Fodelianakis et al, 2021;Jiao & Lu, 2020;Wang, Feng, et al, 2022). Interestingly, less than 1% of comparisons among samples within plots were classified as stochastic processes for ASV data, while about 25% were classified as stochastic processes for OTU data.…”
Section: Discussionsupporting
confidence: 63%
“…In general, homogeneous selection dominates the assembly of prokaryotic communities ( Wang et al, 2022 ). Soil physicochemical properties are the primary determinants of the root-associated construction of the bacterial community, followed by environmental factors, host genotype, and nutrient availability ( Ren et al, 2020 ; Stopnisek and Shade, 2021 ).…”
Section: Discussionmentioning
confidence: 99%